Positively-charged non-magnetic toner and preparation method thereof
By adding a hydrophobic silicon oxide with a specific particle size to the anti -adhesive agent of a specific particle size to the anti -adhesive agent of the hexagonal boron -nitrobine, it has solved the problem of the color tone in the high -temperature and high humidity environment. Stability and print quality.
Patent Information
- Application Number
- CN202411790826.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of printing consumables, and in particular to a positive non-magnetic toner and a preparation method thereof. Background Art
[0002] Positive non-magnetic toner refers to a toner that is positively charged and uses a non-magnetic colorant as a colorant. The positive non-magnetic toner should have appropriate friction charging properties, charging stability, appropriate fluidity and good fixing performance, which is conducive to outputting images with stable color and quality.
[0003] At present, the positive non-magnetic toner in the related art is relatively sensitive to environmental conditions. For example, in a high temperature environment, the binder resin or release agent in the toner changes, causing the toner to agglomerate, which is easy to affect the uniformity of the distribution of the positive non-magnetic toner on the printing drum or paper, thereby affecting the clarity and color density of the print. For another example, in a high humidity environment, the water molecules in the air increase, and the surface of the positive non-magnetic toner absorbs more water, causing the positive non-magnetic toner to agglomerate, which also affects the clarity and color density of the image printed by the positive non-magnetic toner. Summary of the invention
[0004] In order to improve the problem in the related art that positive non-magnetic toner is greatly affected by ambient temperature and humidity and is prone to agglomeration, the present application provides a positive non-magnetic toner and a preparation method thereof.
[0005] In the first aspect, the present application provides a positive non-magnetic toner using the following technical solution: A positive non-magnetic toner comprises 100 parts by weight of a binding resin, 10.8-15.6 parts by weight of a non-magnetic colorant, 4.5-5.5 parts by weight of a positive charge control agent, 1-5 parts by weight of a release agent and 8-10 parts by weight of an anti-adhesive agent, wherein the anti-adhesive agent comprises hydrophobic silica with a particle size range of 40-50 nm and hexagonal boron nitride micropowder with a particle size range of 100-200 nm, and the weight ratio of the hydrophobic silica to the hexagonal boron nitride micropowder is (10-15):1.
[0006] In addition to the basic adhesive resin, non-magnetic colorant, positive charge control agent and release agent, the positive non-magnetic toner of the present application also adds a composition of hydrophobic silica and hexagonal boron nitride powder of a specific particle size as an anti-adhesion aid to prevent the positive non-magnetic toner from adhering. These anti-adhesion aids are wrapped on the outer surface of the positive non-magnetic toner masterbatch, which is beneficial to improve the stability of the positive non-magnetic toner and reduce the impact of the positive non-magnetic toner on the high temperature and high humidity environment. However, it should be noted that the amount of hexagonal boron nitride powder added should not be too high, otherwise it will affect the melt fluidity of the positive non-magnetic toner, which is not conducive to improving the printing quality and printing stability.
[0007] In some specific embodiments, the adhesive resin is a composition of styrene-acrylonitrile copolymer and styrene-2-ethylhexyl acrylate copolymer, and the weight ratio of the styrene-acrylonitrile copolymer to the styrene-2-ethylhexyl acrylate copolymer is (3.5-4.5):1; wherein the glass transition temperature of the styrene-acrylonitrile copolymer is 100-120°C; in the styrene-2-ethylhexyl acrylate copolymer, the weight ratio of styrene and 2-ethylhexyl acrylate monomers is (75-85):(15-25).
[0008] In the present application, the positive non-magnetic toner uses a composition of a styrene-acrylonitrile copolymer and a styrene-2-ethylhexyl acrylate copolymer as a binding resin, and the glass transition temperature of the styrene-acrylonitrile copolymer is controlled to be 100-120°C. In the styrene-2-ethylhexyl acrylate copolymer, the weight ratio of styrene and 2-ethylhexyl acrylate is (75-85): (15-25), which is beneficial to lowering the fixing temperature of the positive non-magnetic toner. At the same time, it can further improve the melt fluidity of the positive non-magnetic toner and reduce the adhesion of the positive non-magnetic toner on the fixing roller.
[0009] In some specific embodiments, the styrene-2-ethylhexyl acrylate copolymer is obtained by reacting styrene and 2-ethylhexyl acrylate monomers in an environment of 78-88° C. for 3-4 hours under the initiation of a peroxidation initiator.
[0010] In some specific embodiments, in the styrene-2-ethylhexyl acrylate copolymer, the weight ratio of styrene and 2-ethylhexyl acrylate is (80-85): (15-20).
[0011] In some specific embodiments, the non-magnetic colorant is at least one of carbon black, cyanine black, monoazo black dye, disazo black dye, and trisazo black dye.
[0012] Carbon black, cyanine black, monoazo black dye, disazo black dye, trisazo black dye, etc. have the advantage of good thermal stability, which is beneficial to improving the color stability of positive non-magnetic toner.
[0013] In some specific embodiments, the positive charge control agent is a styrene-alkyl methacrylate-quaternary ammonium methacrylate monomer copolymer, in which the weight ratio of styrene, alkyl methacrylate, and quaternary ammonium methacrylate monomer is (60-70): (10-15): (20-25).
[0014] In the present application, the positive charge control agent is preferably a styrene-alkyl methacrylate-quaternary ammonium methacrylate monomer copolymer, wherein the positive charge control agent has good compatibility with the binding resin, which is conducive to the uniform dispersion of the positive charge control agent.
[0015] In some specific embodiments, the styrene-alkyl methacrylate-quaternary ammonium methacrylate monomer copolymer is obtained by reacting styrene, alkyl methacrylate, and quaternary ammonium methacrylate monomer in an environment of 82-90° C. for 3-3.5 under the initiation of a peroxidation initiator.
[0016] In some specific embodiments, the methacrylate quaternary ammonium salt monomer is methacryloyloxyethyl trimethyl ammonium chloride.
[0017] In the present application, the positive charge control agent is further preferably styrene-alkyl methacrylate-methacryloyloxyethyl trimethyl ammonium chloride copolymer, which can further reduce the minimum fixing temperature and adhesion of the positive non-magnetic toner, which is beneficial to improving the printing quality and stability of the positive non-magnetic toner.
[0018] In some specific embodiments, the release agent is at least one of paraffin wax, polypropylene wax and polyethylene wax.
[0019] The addition of wax, polypropylene wax and polyethylene wax can improve the anti-offset property of the positive non-magnetic toner, and is beneficial to reducing the adhesion of the positive non-magnetic toner to the fixing roller.
[0020] In the second aspect, the present application provides a method for preparing a positive non-magnetic toner using the following technical solution: A method for preparing a positive non-magnetic toner comprises the following steps: S1, uniformly mixing a binder resin, a non-magnetic colorant, a positive charge control agent and a release agent, melting them uniformly, and then extruding, cooling and pulverizing them to obtain a toner masterbatch; S2. Add an anti-adhesive additive to the toner masterbatch and mix them evenly to obtain a toner.
[0021] The present application adopts the above method to prepare positive non-magnetic toner, which is conducive to obtaining a toner that is less affected by high temperature and high humidity environment and has good stability.
[0022] In some specific embodiments, in step S1, the smelting temperature is 130-140°C.
[0023] In the present application, the smelting temperature is controlled at 130-140° C. to promote uniform mixing of the raw materials.
[0024] In some specific embodiments, the toner masterbatch has a particle size ranging from 10 to 20 μm.
[0025] In the present application, the particle size of the toner master particles is controlled within the range of 10-20 μm, which is beneficial to the melt flow of the positive non-magnetic toner on the one hand, and is beneficial to the uniform and stable attachment of the anti-adhesive additive on the peripheral side of the toner master particles on the other hand.
[0026] In summary, this application at least includes the following beneficial technical effects: (1) In addition to the basic adhesive resin, non-magnetic colorant, positive charge control agent and release agent, the positive non-magnetic toner of the present application also adds a composition of hydrophobic silica and hexagonal boron nitride powder of a specific particle size as an anti-adhesion aid to prevent the positive non-magnetic toner from adhering. These anti-adhesion aids are wrapped on the outer surface of the positive non-magnetic toner masterbatch, which is beneficial to improve the stability of the positive non-magnetic toner and reduce the impact of the positive non-magnetic toner on the high temperature and high humidity environment. However, it should be noted that the amount of hexagonal boron nitride powder added should not be too high, otherwise it will affect the melt fluidity of the positive non-magnetic toner, which is not conducive to improving the printing quality and printing stability.
[0027] (2) In the present application, the positive non-magnetic toner uses a composition of a styrene-acrylonitrile copolymer and a styrene-2-ethylhexyl acrylate copolymer as a binder resin, and the glass transition temperature of the styrene-acrylonitrile copolymer is controlled to be 100-120°C. In the styrene-2-ethylhexyl acrylate copolymer, the weight ratio of styrene and 2-ethylhexyl acrylate is (75-85):(15-25), which is beneficial to lowering the fixing temperature of the positive non-magnetic toner. At the same time, it can further improve the melt fluidity of the positive non-magnetic toner and reduce the adhesion of the positive non-magnetic toner on the fixing roller.
[0028] (3) In the present application, the positive charge control agent is further preferably styrene-alkyl methacrylate-methacryloyloxyethyl trimethyl ammonium chloride copolymer, which can further reduce the minimum fixing temperature and adhesion of the positive non-magnetic toner, and is beneficial to improving the printing quality and stability of the positive non-magnetic toner. DETAILED DESCRIPTION
[0029] The following is a further explanation based on specific experiments. Example
[0030] [Example 1] A positive non-magnetic toner includes 100 kg of a binder resin, 10.8 kg of a non-magnetic colorant, 4.5 kg of a positive charge control agent, 1 kg of a release agent, and 8 kg of an anti-adhesion auxiliary agent.
[0031] In this embodiment, the adhesive resin is a composition of styrene-acrylonitrile copolymer and styrene-2-ethylhexyl acrylate copolymer in a weight ratio of 7:1, wherein the glass transition temperature of the styrene-acrylonitrile copolymer is 105-110°C, and the styrene-2-ethylhexyl acrylate copolymer is obtained by reacting 75kg of styrene and 25kg of 2-ethylhexyl acrylate monomers at 78°C for 4 hours under the initiation of 1.2kg of dibenzoyl peroxide.
[0032] The non-magnetic colorant specifically uses carbon black.
[0033] The positive charge control agent is specifically styrene-dimethylaminoethyl acrylate trimethylammonium chloride copolymer, wherein the styrene-dimethylaminoethyl acrylate trimethylammonium chloride copolymer is obtained by reacting 75kg of styrene and 25kg of dimethylaminoethyl acrylate trimethylammonium chloride at 82°C for 3.5h under the initiation of 1.0kg of dibenzoyl peroxide.
[0034] The release agent is specifically polyethylene wax.
[0035] The anti-adhesive agent specifically comprises hydrophobic silica with a particle size range of 40-50 nm and hexagonal boron nitride powder with a particle size range of 100-200 nm, wherein the weight ratio of the hydrophobic silica to the hexagonal boron nitride powder is 10:1. In this embodiment, the hydrophobic silica is produced by a gas phase method.
[0036] In this embodiment, the preparation method of the positive non-magnetic toner comprises the following steps: S1. After uniformly mixing the binder resin, the non-magnetic colorant, the positive charge control agent and the release agent, the mixture is uniformly melted at 130° C., and then extruded, cooled and crushed to obtain a toner masterbatch with a particle size range of 10-20 μm; S2. Add an anti-adhesive agent to the toner masterbatch, mix them evenly at a stirring speed of 800 r / min, and obtain a toner.
[0037] [Example 2] A positive non-magnetic toner includes 100 kg of a binder resin, 15.6 kg of a non-magnetic colorant, 5.5 kg of a positive charge control agent, 5 kg of a release agent, and 10 kg of an anti-adhesion aid.
[0038] In this embodiment, the adhesive resin is a composition of styrene-acrylonitrile copolymer and styrene-2-ethylhexyl acrylate copolymer in a weight ratio of 7:1, wherein the glass transition temperature of the styrene-acrylonitrile copolymer is 110-120°C, and the styrene-2-ethylhexyl acrylate copolymer is obtained by reacting 85kg of styrene and 20kg of 2-ethylhexyl acrylate monomers at 88°C for 3h under the initiation of 1.2kg of dibenzoyl peroxide.
[0039] The non-magnetic colorant is specifically cyanine black.
[0040] The positive charge control agent is specifically styrene-dimethylaminoethyl acrylate trimethylammonium chloride copolymer, wherein the styrene-dimethylaminoethyl acrylate trimethylammonium chloride copolymer is obtained by reacting 80kg of styrene and 20kg of dimethylaminoethyl acrylate trimethylammonium chloride at 90°C for 3h under the initiation of 1.5kg of dibenzoyl peroxide.
[0041] The release agent specifically adopts polypropylene wax.
[0042] The anti-adhesive agent specifically comprises hydrophobic silica with a particle size range of 40-50 nm and hexagonal boron nitride powder with a particle size range of 100-200 nm, wherein the weight ratio of the hydrophobic silica to the hexagonal boron nitride powder is 15:1. In this embodiment, the hydrophobic silica is produced by a gas phase method.
[0043] In this embodiment, the preparation method of the positive non-magnetic toner comprises the following steps: S1, after uniformly mixing the binding resin, non-magnetic colorant, positive charge control agent and release agent, melting them uniformly at 140°C, and then extruding, cooling and crushing them to obtain a toner masterbatch with a particle size range of 10-20 μm; S2. Add an anti-adhesive agent to the toner masterbatch, mix them evenly at a stirring speed of 850 r / min, and obtain a toner.
[0044] [Example 3] A positive non-magnetic toner, which is different from Example 1 in that the binder resin is different. In this example, the binder resin is a composition of styrene-acrylonitrile copolymer and styrene-2-ethylhexyl acrylate copolymer in a weight ratio of 3.5:1.
[0045] [Example 4] A positive non-magnetic toner, which is different from Example 1 in that the binder resin is different. In this example, the binder resin is a composition of styrene-acrylonitrile copolymer and styrene-2-ethylhexyl acrylate copolymer in a weight ratio of 4.5:1.
[0046] [Example 5] A positive non-magnetic toner, which differs from Example 4 in that the positive charge control agent is different. In this example, the positive charge control agent is a styrene-methacryloyloxyethyl trimethyl ammonium chloride copolymer, which is obtained by reacting 75 kg of styrene and 25 kg of methacryloyloxyethyl trimethyl ammonium chloride at 82° C. for 3.5 hours under the initiation of 1.0 kg of dibenzoyl peroxide.
[0047] [Example 6] A positive non-magnetic toner, which differs from Example 4 in that the positive charge control agent is different. In this example, the positive charge control agent is styrene-ethyl methacrylate-methacryloyloxyethyl trimethyl ammonium chloride copolymer, which is obtained by reacting 60 kg of styrene, 15 kg of ethyl methacrylate and 25 kg of methacryloyloxyethyl trimethyl ammonium chloride at 82°C for 3.5 hours under the initiation of 1.0 kg of dibenzoyl peroxide.
[0048] [Example 7] A positive non-magnetic toner, which differs from Example 4 in that the positive charge control agent is different. In this example, the positive charge control agent is styrene-ethyl methacrylate-methacryloyloxyethyl trimethyl ammonium chloride copolymer, which is obtained by reacting 70 kg of styrene, 10 kg of ethyl methacrylate and 20 kg of methacryloyloxyethyl trimethyl ammonium chloride at 88°C for 3 hours under the initiation of 1.5 kg of dibenzoyl peroxide.
[0049] [Example 8] A positive non-magnetic toner, which differs from Example 7 in that the positive charge control agent is different. In this example, the positive charge control agent is styrene-ethyl methacrylate-methacryloyloxyethyl trimethyl ammonium chloride copolymer, which is obtained by reacting 70 kg of styrene, 20 kg of ethyl methacrylate and 10 kg of methacryloyloxyethyl trimethyl ammonium chloride at 88°C for 3 hours under the initiation of 1.5 kg of dibenzoyl peroxide.
[0050] Comparative Example [Comparative Example 1] A positive non-magnetic toner, which is different from Example 1 in that the anti-adhesion aid is different. In this comparative example, the anti-adhesion aid is hydrophobic silica with a particle size range of 40-50 nm, and the hydrophobic silica is prepared by a gas phase method.
[0051] [Comparative Example 2] A positive non-magnetic toner, which differs from Example 1 in that the anti-adhesion aid is different. In this comparative example, the anti-adhesion aid is hexagonal boron nitride micropowder with a particle size range of 100-200 nm.
[0052] [Comparative Example 3] A positive non-magnetic toner, which differs from Example 1 in that an anti-adhesive agent is different. In this comparative example, the anti-adhesive agent is a composition of hydrophobic silica with a particle size range of 40-50 nm and hexagonal boron nitride micropowder with a particle size range of 100-200 nm, wherein the weight ratio of the hydrophobic silica to the hexagonal boron nitride micropowder is 4:1.
[0053] [Comparative Example 4] A positive non-magnetic toner, which differs from Example 1 in that no anti-adhesive additive is added.
[0054] Performance testing 1. Heat resistance stability: The positive non-magnetic toners prepared in each embodiment and comparative example were placed in an environment with a constant temperature of 80°C, left to stand for 72 hours, and then cooled. The residual rate of the positive non-magnetic toners in each embodiment and comparative example before and after heating was tested on a 200-mesh sieve, and the difference between the residual rate of the positive non-magnetic toner after heating and the residual rate of the positive non-magnetic toner before heating was recorded. The larger the difference a, the larger the agglomeration ratio of the positive non-magnetic toner and the worse the heat resistance stability. In this application, the difference a less than 2% is qualified.
[0055] 2. Moisture resistance stability: The positive non-magnetic toners prepared in each embodiment and comparative example were placed in an environment with a constant temperature of 25°C and a humidity of 90% and left to stand for 168 hours. The residual rate of the positive non-magnetic toners in each embodiment and comparative example when passing through a 200-mesh sieve before and after the moisture resistance test was tested respectively, and the difference between the residual rate of the positive non-magnetic toner after the moisture resistance test and the residual rate of the positive non-magnetic toner before the moisture resistance test was recorded. The larger the difference b, the larger the agglomeration ratio of the positive non-magnetic toner and the worse the moisture resistance stability. In this application, the difference b less than 2% is qualified.
[0056] 3. Evaluation of printing image effect: The positive non-magnetic toner prepared in each embodiment and comparative example is added to the toner cartridge of the printer, and the temperature of the fixing roller is raised from 140°C to 180°C to perform a fixing test. During the fixing test, if the fixing effect is unsatisfactory, the temperature is raised by 10°C and the fixing is performed again. If the fixing effect is qualified, the lowest temperature corresponding to the qualified fixing is recorded.
[0057] 4. Printing image stability: The positive non-magnetic toner prepared in each embodiment and comparative example is added to the toner cartridge of the printer. In an environment with a temperature of 25°C and a humidity of 75%, the temperature of the fixing roller is controlled to be 180°C. 2,000 images with a printing rate of 5% are continuously printed. The color density value and the bottom gray value of the first and 10,000th images are compared. The higher the color density value, the clearer the printed image and the richer the details; the lower the bottom gray value, the cleaner the background and the less unnecessary gray or dirt. In this application, a color density value of more than 1.35 and a bottom gray value of less than 2 are considered qualified. In addition, after printing, the amount of positive non-magnetic toner adhered to the fixing roller is measured.
[0058] Table 1 Table 2 Combining Example 1 with Comparative Examples 1-4 and the test results in Table 1-2, it can be seen that the hydrophobic silica of different particle sizes and hexagonal boron nitride powder are compounded in a specific ratio as an anti-adhesion and anti-adhesion auxiliary agent, which can effectively improve the stability of the positive non-magnetic toner under high temperature and high humidity conditions, and is beneficial to improving the printing stability. In addition, when the hydrophobic silica is coated on the outer surface of the toner masterbatch alone, it is easy to cause the fixing temperature of the positive non-magnetic masterbatch to increase. When a certain proportion of hexagonal boron nitride powder with good thermal conductivity is used, it is beneficial to reduce the fixing temperature of the positive non-magnetic masterbatch.
[0059] Combining Example 1 with Examples 3-4 and the test results in Table 1-2, it can be seen that in the adhesive, the weight ratio of styrene-acrylonitrile copolymer to styrene-2-ethylhexyl acrylate copolymer is in the range of (3.5-4.5):1, which is beneficial to improving the minimum fixing temperature of the positive non-magnetic toner, and can reduce the adhesion of the positive non-magnetic toner on the fixing roller and improve the bottom gray value of the positive non-magnetic toner when printing.
[0060] In combination with Example 4 to Example 8 and the test results in Table 1-2, it can be seen that the positive charge control agent is preferably a styrene-alkyl methacrylate-quaternary ammonium methacrylate monomer copolymer prepared by three monomers of styrene, alkyl methacrylate, and quaternary ammonium methacrylate in a weight ratio of (60-70): (10-15): (20-25). It can not only obtain the lowest fixing temperature before coating and modification with the positive non-magnetic toner, but also can further reduce the adhesion of the positive non-magnetic toner, which is beneficial to improving the printing stability of the positive non-magnetic toner.
[0061] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A positive non-magnetic toner, characterized in that: The invention comprises 100 parts by weight of a binder resin, 10.8-15.6 parts by weight of a non-magnetic colorant, 4.5-5.5 parts by weight of a positive charge control agent, 1-5 parts by weight of a release agent and 8-10 parts by weight of an anti-adhesive agent, wherein the anti-adhesive agent comprises hydrophobic silica with a particle size range of 40-50 nm and hexagonal boron nitride powder with a particle size range of 100-200 nm, and the weight ratio of the hydrophobic silica to the hexagonal boron nitride powder is (10-15):
1.
2. A positive non-magnetic toner according to claim 1, characterized in that: The adhesive resin is a composition of styrene-acrylonitrile copolymer and styrene-2-ethylhexyl acrylate copolymer, wherein the weight ratio of the styrene-acrylonitrile copolymer to the styrene-2-ethylhexyl acrylate copolymer is (3.5-4.5):1; wherein the glass transition temperature of the styrene-acrylonitrile copolymer is 100-120°C; and in the styrene-2-ethylhexyl acrylate copolymer, the weight ratio of styrene and 2-ethylhexyl acrylate monomers is (75-85):(15-25).
3. A positive non-magnetic toner according to claim 2, characterized in that: In the styrene-2-ethylhexyl acrylate copolymer, the weight ratio of styrene and 2-ethylhexyl acrylate is (80-85): (15-20).
4. A positive non-magnetic toner according to any one of claims 2 to 3, characterized in that: The positive charge control agent is a styrene-alkyl methacrylate-quaternary ammonium methacrylate monomer copolymer, in which the weight ratio of styrene, alkyl methacrylate and quaternary ammonium methacrylate monomer is (60-70): (10-15): (20-25).
5. A positive non-magnetic toner according to claim 4, characterized in that: The methacrylic acid quaternary ammonium salt monomer is methacryloyloxyethyl trimethyl ammonium chloride.
6. A positive non-magnetic toner according to any one of claims 1 to 3, characterized in that: The non-magnetic colorant is at least one of carbon black, cyanine black, monoazo black dye, disazo black dye and trisazo black dye.
7. A positive non-magnetic toner according to any one of claims 1 to 3, characterized in that: The release agent is at least one of paraffin wax, polypropylene wax and polyethylene wax.
8. A method for preparing a positive non-magnetic toner according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, uniformly mixing a binder resin, a non-magnetic colorant, a positive charge control agent and a release agent, melting them uniformly, and then extruding, cooling and crushing them to obtain a toner masterbatch; S2. Add an anti-adhesive additive to the toner masterbatch and mix them evenly to obtain a toner.
9. The method for preparing a positive non-magnetic toner according to claim 8, characterized in that: In step S1, the melting temperature is 130-140°C.
10. The method for preparing a positive non-magnetic toner according to claim 8, characterized in that: The particle size of the toner masterbatch is in the range of 10-20 μm.
Citation Information
Patent Citations
Positively-charged non-magnetic toner and preparation method thereof
CN119148484A